Automatic depth control system for a no-till seeder - Zhao, Jiale; Zhu, Longtu; Jia, Honglei; Huang, Dongyan; Guo, Mingzhuo; Cong, Yongjiang (International Journal of Agricultural and Biological Engineering, 2018)
Sowing depth has an important impact on the performance of a no-till seeder. The seeds should be placed at optimal depth for rapid germination and emergency. To compensate the spatial variation in soil type and conditions, an automatic depth control system was designed, which consisted of a deformation sensor, an actuator and a controller. The deformation sensor was made of polyvinylidene fluoride (PVDF) film, which was fixed on the inner surface of the gauge wheel, and the output voltage was determined by the deformation of the wheel. Two models of the PVDF sensor with a tiled shape and an arched shape were set up to analyze the relationship between the output signal and the wheel deformation. In the experiments, the relationship between the output voltage and gauge wheel deformation was obtained, and the results were in accord with the model analysis results. The voltage of both sensors increase with the augment of deformation, the arched sensor was more sensitive than the tiled one. The arched sensor embedded in the control system was able to maintain the desired seeding depth within tolerance ±8 mm at driving speed of 2.78 m/s, which can satisfy the agronomic requirements for the no-till seeder.Keywords: no-till seeder, sowing depth, control system, polyvinylidene fluoride (PVDF) film, sensorDOI: 10.25165/j.ijabe.20181101.3229Citation: Zhao J L, Zhu L T, Jia H L, Huang D Y, Guo M Z, Cong Y J. Automatic depth control system for a no-till seeder. Int J Agric & Biol Eng, 2018; 11(1): 115–121.